KETELADANAN LIMA PRIBADI MULIA DALAM SYI’IR “LI KHOMSATUN”: KAJIAN SEMIOTIKA ROLAND BARTHES - Fatimah Isyti Karimah; Dadan Rusmana; Wildan Taufik (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2022)
This research aims to comprehend the meaning of syi‟ir (song) “Li Khomsatun” in the context of five role model personalities by using Roland Barthes‟ semiotics theory. The method used in this research is qualitative descriptive analysis. The results show that Syi'ir li khomsatun in Javanese language recently used by Indonesians as a prayer to prevent the COVID-19 virus outbreak, evidently it contains a deep meaning about five worthy personalities deserving to become role models by describing the exemplary characters. Moreover, this article reveals other arguments such as Qs. al-Ahzab: 33, hadith thaqalayn, hadith kisa' and a brief interpretation of Surah Al-Insan verses 7—10 to support the worthiness of the five noble persons or Ahlulbait of the Prophet as a role model. He also becomes an intermediary to avert human being from miseries in the world and in the hereafter.